Antimicrobial susceptibility and pulsed-field gel electrophoresis of shigella sonnei strains in Malaysia (1997-2000) - Hoe, C.H.; Yasin, R.M.; Koh, Y.T.; Thong, Kwai Lin (Wiley, 2005)
Aims: Antimicrobial resistance of Shigella sonnei from Malaysia was determined and subtyping was carried by pulsed- field gel electrophoresis ( PFGE) to assess the extent of genetic diversity of these strains. Methods and Results: A total of 62 isolates of S. sonnei from sporadic cases of shigellosis in different parts of Malaysia were studied by antimicrobial susceptibility test and PFGE. Approximately 35.5 of the strains showed resistance to three or more antimicrobial agents. Eight resistant phenotypes, i. e. RI to RVIII, was defined. Resistant phenotype RV and RVIII only appeared in year 2000. PFGE analysis with NotI and XbaI restriction showed that a great heterogeneity existed at the DNA level among Malaysian S. sonnei isolates. Fifty- eight NotI and 61 XbaI- PFGE profiles were observed in 63 S. sonnei isolates, including ATCC 11060 isolate. Drug sensitive isolates displayed very different profiles from drug- resistant isolates, with a few exceptions. Isolates of resistant phenotype RVI ( SXTr. TETr. STRr) showed a greater similarity among each other compared with isolates of resistant phenotype RI and drug- sensitive isolates. Conclusion: Multi- drug- resistant S. sonnei were circulated in different parts of Malaysia and the emergence of new resistant phenotype was observed. Wide genetic variations among Malaysian S. sonnei were observed and the drug- sensitive strains could be differentiated from drug- resistant strains by PFGE. Significance and Impact of the Study: The present study verifies the usefulness of PFGE in characterizing and comparing strains of S. sonnei. Minor variations among S. sonnei isolates could be detected by PFGE.